2007
DOI: 10.1016/s1726-4901(09)70296-5
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of Sinonasal Mucosal Melanoma: Clinical Review of 23 Cases

Abstract: In our experience, primary sinonasal mucosa melanoma is prone to spread from the site of origin. The major obstacle in improving overall survival is achieving systemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 23 publications
5
38
0
1
Order By: Relevance
“…[ Table 1] There are conflicting reports regarding the incidence of sinonasal mucosal melanoma in males and females. 6,8,26,[40][41][42][43] The male/female ratio of our patients was 8, which is consistent with the study by Richtig et al 6 However, in the literature review, by analyzing the data of the reported series, the mean male/female ratio of 843 patients was 1.07 and we did not find significant differences. [ Table 1]…”
Section: Discussionsupporting
confidence: 91%
“…[ Table 1] There are conflicting reports regarding the incidence of sinonasal mucosal melanoma in males and females. 6,8,26,[40][41][42][43] The male/female ratio of our patients was 8, which is consistent with the study by Richtig et al 6 However, in the literature review, by analyzing the data of the reported series, the mean male/female ratio of 843 patients was 1.07 and we did not find significant differences. [ Table 1]…”
Section: Discussionsupporting
confidence: 91%
“…However, there is no universally accepted provision for paranasal sinus melanoma staging within the TNM system according to Cheng and Lai's 2007 article "Towards a Better Understanding of Sino Nasal Mucosal Melanoma" [6] . Most clinicians use a simplified three-stage system: stage Ⅰ for localized disease, stage Ⅱ for lymph node metastases, and stage Ⅲ for distant metastasis [1] .…”
Section: Stagingmentioning
confidence: 99%
“…Even though traditionally these tumors were known to be radioresistant, some investigations suggest the use of radiation therapy after resection of mucosal melanoma [1] . Therefore, complete surgical removal of tumor and postoperative radiation therapy is the standard of care for resectable lesions [5,6] . Clinical data has proven that combining chemotherapy (either intraarterial or intravenous) along with radiation therapy may improve local control of paranasal sinus tumors.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Так, у японцев частота встречаемости МСО на-много выше (8 % всех меланом) по сравнению с пока-зателями у пациентов европеоидной расы (1 %) [21][22][23][24]. Более того, 7,5 % всех меланом у японцев развиваются в полости рта (1 % у пациентов европеоидной расы) [25,26].…”
Section: этиопатогенезunclassified